The Influence of Brand Image on Brand Trust and Its Impact on Brand Loyalty (Study of MS Glow Consumers in Malang City) - Pramesti, Galuh Cahyaning; Marsudi; Andharani, Sri Nastiti (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to examine the influence of brand image on brand loyalty through brand trust as an intervening variable. The type of research used is explanatory research using a quantitative approach and research conducted by survey using non-probability sampling techniques and purposive sampling sampling techniques as many as 120 consumer respondents from MS Glow. The Data were analyzed using Partial Least Square. From the results of the study can be concluded that 1) brand image has a positive and significant effect on brand loyalty 2) brand image has a positive and significant effect on brand trust 3) Brand Trust has a positive and significant effect on brand loyalty 4) brand image has an effect on brand loyalty mediated by Brand Trust as an intervening variable.